In vitro culture and characterization of human lung cancer circulating tumor cells isolated by size exclusion from an orthotopic nude-mouse model expressing fluorescent protein - Kolostova, Katarina; Zhang, Yong; Hoffman, Robert M; Bobek, Vladimir (Journal of fluorescence, 2014)
In the present study, we demonstrate an animal model and recently introduced size-based exclusion method for circulating tumor cells (CTCs) isolation. The methodology enables subsequent in vitro CTC-culture and characterization. Human lung cancer cell line H460, expressing red fluorescent protein (H460-RFP), was orthotopically implanted in nude mice. CTCs were isolated by a size-based filtration method and successfully cultured in vitro on the separating membrane (MetaCell®), analyzed by means of time-lapse imaging. The cultured CTCs were heterogeneous in size and morphology even though they originated from a single tumor. The outer CTC-membranes were blebbing in general. Abnormal mitosis resulting in three daughter cells was frequently observed. The expression of RFP ensured that the CTCs originated from lung tumor. These readily isolatable, identifiable and cultivable CTCs can be used to characterize individual patient cancers and for screening of more effective treatment.
Keywords: zvířata; Porosity; Lung Neoplasms; nádorové cirkulující buňky; Surface Properties; Tumor Cells, Cultured; Particle Size; Mice; velikost částic; Animals; Cell Separation; nádory plic; myši nahé; Disease Models, Animal; poréznost; transplantace nádorů; Mice, Nude; Neoplastic Cells, Circulating; Neoplasm Transplantation; modely nemocí na zvířatech; nádorové buňky kultivované; separace buněk; luminescentní proteiny; lidé; Humans; povrchové vlastnosti; myši; Luminescent Proteins